A method and device for preparing lyocell cross-linked fiber
By spraying a mixed liquid of crosslinking agent and catalyst on the fiber ribbon, the problem of crosslinking agent hydrolysis and self-polymerization in traditional fiber crosslinking is solved, which improves the crosslinking effect and reduces production costs.
Patent Information
- Application Number
- CN202110698763.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-06-23
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2041-06-23
AI Technical Summary
During the traditional fiber cross-linking process, cross-linking agents are prone to hydrolysis or self-polymerization, resulting in a decrease in cross-linking effect and an increase in production costs.
Hydrolysis and self-polymerization of the crosslinking agent are prevented by spraying the crosslinking agent solution and the catalyst solution immediately after mixing it and curing.
It effectively improves the cross-linking effect, reduces production costs, and simplifies equipment requirements and operating procedures.
Smart Images

Figure BDA0003128892630000081 
Figure HDA0003128892640000011 
Figure HDA0003128892640000012
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cross-linked fibers, and in particular relates to a preparation method and a device for cross-linked lyocell fibers. Background Art
[0002] Traditional fiber crosslinking is a reaction between a crosslinking agent and fiber under the activation of a catalyst. In this process, some crosslinking agents are prone to hydrolysis or self-polymerization after being activated, resulting in a decrease in the crosslinking effect, a waste of crosslinking agents, and an increase in production costs. Taking the existing crosslinking equipment as an example, when the crosslinking temperature is 80°C, the TAHT (1,3,5-triacryloylhexahydro-1,3,5-triazine) solution concentration is 0.92%wt, and the NaOH concentration is 0.2%wt, the crosslinking agent hydrolysis rate reaches 11.04g / (L*h). In production, in order to achieve a stable crosslinking effect, it is necessary to continuously add crosslinking agents and catalysts to the crosslinking bath. With a TAHT of about 110,000 / t and a crosslinking agent storage tank of 3m 3 It is calculated that the cross-linking agent hydrolysis costs about 31.914 million yuan each year. This greatly increases the production cost. In the process of cross-linking fibers, HMMM (methyl etherified hexahydroxymethyl melamine resin) is easily self-polymerized under the influence of sulfonic acid catalyst to form hard solid precipitates, which not only increases production costs, but also the precipitates are easy to block pipelines, affecting the normal production. Summary of the invention
[0003] In view of this, the object of the present invention is to provide a method and device for preparing lyocell cross-linked fibers. The method provided by the present invention can prevent the cross-linking agent from hydrolyzing and self-polymerizing during the preparation of lyocell cross-linked fibers.
[0004] The present invention provides a method for preparing a lyocell cross-linked fiber, comprising:
[0005] The crosslinking liquid formed by mixing the crosslinking agent solution and the catalyst solution is immediately sprayed on the fiber ribbon, and then the sprayed fiber ribbon is cured to obtain Lyocell crosslinked fiber.
[0006] Preferably, before the curing process, the process further comprises:
[0007] The fiber ribbon after spraying is subjected to extrusion treatment;
[0008] During the process between spraying and squeezing, the fiber ribbon moves from bottom to top in a direction parallel to the fiber ribbon, so that the squeezed cross-linking liquid naturally flows downward along the fiber ribbon.
[0009] Preferably, before the spraying, the method further comprises:
[0010] The fiber ribbon is divided into at least two fiber sub-ribbons, each of which has two sides; and during the spraying process, the cross-linking liquid is sprayed on both sides of each fiber sub-ribbon.
[0011] Preferably, the crosslinking agent in the crosslinking agent solution is selected from 1,3,5-triacryloylhexahydro-1,3,5-triazine; and the catalyst in the catalyst solution is selected from one or more of sodium hydroxide, trisodium phosphate and sodium carbonate.
[0012] Preferably, the crosslinking agent in the crosslinking agent solution is selected from methylated hexamethylolmelamine resin; the catalyst in the catalyst solution is selected from one or more of methanesulfonic acid, p-toluenesulfonic acid and dodecylbenzenesulfone.
[0013] Preferably, the mass ratio of the fiber ribbon, the crosslinking agent in the crosslinking agent solution, and the catalyst in the catalyst solution is 100:(0.1-7):(0.1-13).
[0014] Preferably, the mass ratio of the fiber ribbon, the crosslinking agent in the crosslinking agent solution, and the catalyst in the catalyst solution is 100:(0.1-10):(0.6-8).
[0015] Preferably, the temperature of the fiber ribbon during the process between spraying and curing is 65-85°C.
[0016] Preferably, it also includes:
[0017] Sodium sulfate was added to the crosslinker solution.
[0018] The present invention provides a preparation device for Lyocell cross-linked fibers, comprising:
[0019] A spray chamber, used to spray the cross-linking liquid on the fiber ribbons;
[0020] A curing device having an inlet connected to the outlet of the spray chamber, wherein the fiber ribbon enters the curing device from the spray chamber;
[0021] The inlet of the water washing tank is connected to the outlet of the curing device, and the fiber ribbon enters the water washing tank from the curing device.
[0022] Preferably, the spray chamber is arranged vertically, so that the fiber ribbon enters the spray chamber and is transported from bottom to top in the vertical direction along the bottom to the top of the spray chamber.
[0023] Preferably, a distribution assembly is provided at the bottom end of the spray chamber so that the fiber ribbon is distributed into at least two fiber sub-ribbons after entering the spray chamber.
[0024] Preferably, a plurality of nozzles are arranged in the spray chamber, and nozzles are arranged on both sides of each fiber sub-ribbon.
[0025] Preferably, a temperature control system for adjusting the temperature in the spray chamber is provided in the spray chamber.
[0026] The method provided by the present invention can prevent the hydrolysis and self-polymerization of the crosslinking agent in the process of preparing crosslinked fibers, solves the problem of large-scale waste of crosslinking liquid caused by mixed hydrolysis and self-polymerization of the crosslinking agent and the catalyst, has low equipment requirements and is simple to operate, effectively improves the crosslinking effect, and reduces production costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is a schematic diagram of the structure of a device for preparing cross-linked fibers in the prior art;
[0028] Figure 2 Schematic diagram of the structure of a device for preparing cross-linked fibers in an embodiment of the present invention;
[0029] Figure 3 Schematic diagram of the structure of the spray chamber in an embodiment of the present invention. DETAILED DESCRIPTION
[0030] The technical solutions in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other examples improved or modified by ordinary technicians in this field belong to the scope of protection of the present invention. It should be understood that the embodiments of the present invention are only used to illustrate the technical effects of the present invention, rather than to limit the scope of protection of the present invention. In the embodiments, the methods used are conventional methods unless otherwise specified.
[0031] The present invention provides a method for preparing a lyocell cross-linked fiber, comprising:
[0032] The crosslinking liquid formed by mixing the crosslinking agent solution and the catalyst solution is immediately sprayed on the fiber ribbon, and then the sprayed fiber ribbon is cured to obtain Lyocell crosslinked fiber.
[0033] In the present invention, the crosslinking agent solution and the catalyst solution are mixed to form a crosslinking liquid, which is immediately sprayed on the fiber ribbon after the crosslinking liquid is formed. The time from the formation of the crosslinking liquid (including the time for the crosslinking agent solution and the catalyst solution to be mixed) to the time when the crosslinking liquid is sprayed on the fiber ribbon is preferably not more than 10 seconds, more preferably 1 to 9 seconds, more preferably 2 to 8 seconds, more preferably 3 to 6 seconds, and most preferably 4 to 5 seconds.
[0034] In the present invention, the shorter the mixing time of the crosslinking agent and the catalyst before the crosslinking liquid is sprayed on the fiber ribbon, the better, so that the crosslinking agent can be significantly reduced in hydrolysis or self-polymerization. Compared with the immersion crosslinking in the prior art, the crosslinked fiber prepared by the method provided by the present invention has a comparable wet wear value, but unexpectedly greatly reduces the amount of crosslinking agent used, significantly reducing the preparation cost of the crosslinked fiber. The method provided by the present invention not only shortens the mixing time of the crosslinking agent and the catalyst before spraying to reduce hydrolysis or self-polymerization, but also once the crosslinking liquid is sprayed on the surface of the fiber ribbon, it effectively inhibits the adverse effects of the catalyst on the crosslinking agent.
[0035] In the present invention, the curing treatment preferably further comprises:
[0036] The fiber ribbon after spraying is subjected to extrusion treatment; during the process between spraying and extrusion, the fiber ribbon moves from bottom to top in a direction parallel to the fiber ribbon, so that the extruded cross-linking liquid flows naturally downward along the fiber ribbon. In the present invention, the best arrangement of the fiber ribbon during the process between spraying and extrusion is vertical arrangement, which can ensure that the extruded cross-linking liquid flows smoothly downward along the fiber ribbon, but the arrangement of the fiber ribbon in the present invention is not limited to this, and the fiber ribbon can also have a certain inclination angle according to actual process requirements, as long as it is ensured that the extruded cross-linking liquid can still flow on the fiber ribbon and does not drip from the fiber ribbon.
[0037] In the present invention, the spraying process is preferably arranged below the extrusion process. When the fiber ribbon after spraying enters the extrusion process, it is preferably transported from the spraying process from bottom to top to the extrusion process in a direction parallel to the fiber ribbon. When the fiber ribbon is extruded, the squeezed cross-linking liquid naturally flows downward along the fiber ribbon. Since the squeezed cross-linking liquid naturally flows downward along the fiber ribbon under the action of gravity, the cross-linking liquid and the fiber ribbon can be more fully and evenly bonded, and the cross-linking liquid is promoted to be evenly immersed in the gaps of the fiber ribbon; and the cross-linking liquid squeezed out by the extrusion roller re-participates in the immersion cross-linking of the fiber ribbon, further improving the utilization rate of the cross-linking liquid.
[0038] In the present invention, the spraying preferably further comprises:
[0039] The fiber ribbon is divided into at least two fiber sub-ribbons, each of which has two sides; and during the spraying process, the cross-linking liquid is evenly sprayed on both sides of each fiber sub-ribbon.
[0040] In the present invention, the fiber ribbon is preferably divided into at least two fiber sub-ribbons, more preferably three fiber sub-ribbons, each fiber sub-ribbon having two sides, and during the spraying process, both sides of each fiber sub-ribbon are evenly sprayed with the cross-linking liquid.
[0041] In the present invention, before the extrusion, a plurality of fiber sub-ribbons are preferably gathered to form a fiber ribbon and then extruded.
[0042] The present invention can further improve the impregnation effect of the cross-linking liquid and the fiber ribbon through the above operation. First, the fiber ribbon is divided into two or more sub-ribbons, and each sub-ribbon is sprayed with the cross-linking liquid, so that the fiber ribbon is in more sufficient contact with the cross-linking liquid; secondly, the sub-ribbons are gathered into a set of squeezing rollers to be squeezed into a fiber ribbon. In this way, at the moment of squeezing, the cross-linking liquid penetrates from the inside and outside of the fiber ribbon at the same time, thereby improving the fiber impregnation effect; thirdly, this can reduce the amount of cross-linking liquid sprayed on the surface of each sub-ribbon, so that a relatively thin cross-linking liquid layer is formed on the surface of the sub-ribbon, and unexpectedly reduces the adverse effect of the catalyst on the cross-linking agent.
[0043] In the present invention, during the spraying process, the sprayed cross-linking liquid is preferably allowed to penetrate the fiber ribbon horizontally and spray on both sides of the fiber ribbon, or both sides of each fiber sub-ribbon, so that the cross-linking liquid can be sprayed on the fiber ribbon more evenly.
[0044] The present invention has no special restrictions on the method of the extrusion treatment, and the fiber ribbon can be extruded by a roller (extrusion roller) using an extrusion method well known to those skilled in the art. In the present invention, the extrusion treatment adjusts the rolling ratio by adjusting the pressure of the extrusion roller, and the rolling ratio is preferably 100% to 180%.
[0045] In the present invention, when the crosslinking agent in the crosslinking agent solution is preferably selected from 1,3,5-triacryloylhexahydro-1,3,5-triazine (TAHT for short), the concentration of the crosslinking agent solution is preferably 0.1-6%wt, more preferably 0.5-5%wt, more preferably 1-4%wt, more preferably 2-3%wt, and most preferably 2.5%wt; the catalyst in the catalyst solution is preferably selected from one or more of sodium hydroxide, trisodium phosphate and sodium carbonate; the concentration of the catalyst solution is preferably 0.1-1%wt, more preferably 0.2-0.8%wt, more preferably 0.3-0.6%wt, and most preferably 0.4-0.5%wt; the temperature of the fiber ribbon during the process between spraying and curing treatment is preferably 65-85°C, more preferably 70-82°C, and most preferably 80°C; The cross-linking solution preferably also includes sodium sulfate; sodium sulfate is preferably added to the cross-linking agent solution, and then mixed with the catalyst solution to form a cross-linking solution. In the present invention, the addition of sodium sulfate can promote the adsorption and bonding of the cross-linking agent THAT with the fiber ribbon; the mass ratio of the fiber ribbon to sodium sulfate is preferably 100: (1-13), more preferably 100: (3-10), more preferably 100: (5-8), and most preferably 100: (6-7); the mass ratio of the fiber ribbon, the cross-linking agent in the cross-linking agent solution, and the catalyst in the catalyst solution is preferably 100: (0.1-7): (0.1-13), more preferably 100: (0.5-6): (0.5-10), more preferably 100: (1-5): (1-8), more preferably 100: (2-4): (3-6), and most preferably 100: 3: (4-5).
[0046] In the present invention, when the crosslinking agent in the crosslinking agent solution is preferably selected from methylated hexamethylol melamine resin (HMMM for short), the concentration of the crosslinking agent solution is preferably 1-6%wt, more preferably 2-5%wt, more preferably 3-4%wt, and most preferably 3.5%wt. The catalyst in the catalyst solution is preferably selected from one or more of methanesulfonic acid, p-toluenesulfonic acid and dodecylbenzenesulfone; the concentration of the catalyst solution is preferably 0.5-6%wt, more preferably 1-5%wt, more preferably 2-4%wt, and most preferably 3%wt. ; The temperature of the fiber ribbon during the process between spraying and curing treatment is preferably 18-40°C, more preferably 20-35°C, and most preferably 25-30°C; the mass ratio of the fiber ribbon, the crosslinker in the crosslinker solution, and the catalyst in the catalyst solution is preferably 100:(0.1-10):(0.6-8), more preferably 100:(0.5-9):(1-7), more preferably 100:(1-8):(2-6), more preferably 100:(3-6):(3-5), and most preferably 100:(4-5):4.
[0047] In the present invention, the mass ratio of the crosslinking solution (a mixture of a crosslinking agent solution and a catalyst solution) to the fiber ribbon is preferably (0.33-1.31):1, more preferably (0.92-1.12):1, and most preferably 1.03:1.
[0048] In the present invention, the solvent in the cross-linking agent solution is preferably selected from water; the solvent in the catalyst solution is preferably selected from water.
[0049] In the present invention, the fiber ribbon is preferably a Lyocell fiber ribbon.
[0050] In the present invention, the temperature of the curing treatment is preferably 80-160°C, more preferably 100-140°C, more preferably 110-130°C, and most preferably 120°C; the time of the curing treatment is preferably 5-60min, more preferably 10-50min, more preferably 20-40min, and most preferably 30min.
[0051] In the present invention, after the curing is completed, it is preferred that the following steps are further included:
[0052] The solidified product is washed with water and dried to obtain cross-linked fibers with anti-fibrillation ability.
[0053] In the present invention, the drying temperature is preferably 65-90°C, more preferably 70-85°C, most preferably 75-80°C.
[0054] The method provided by the present invention solves the problem of large amount of crosslinking liquid wasted due to mixed hydrolysis and self-polymerization of the crosslinking agent and the catalyst, has low equipment requirements and simple operation, effectively improves the crosslinking effect and reduces production costs.
[0055] The present invention provides a preparation device for lyocell cross-linked fibers, the structural schematic diagram of which is shown in FIG. Figure 2 As shown, including:
[0056] A spray chamber 4, used for spraying a cross-linking liquid on the fiber ribbon;
[0057] A curing device 5 having an inlet connected to the outlet of the spray chamber, wherein the fiber ribbon enters the curing device from the spray chamber;
[0058] A water washing tank 6 whose inlet is connected to the outlet of the curing device, and the fiber ribbon enters the water washing tank from the curing device.
[0059] In the present invention, the spray chamber is preferably arranged vertically so that the fiber ribbon between the front end (bottom end) and the end (top end) of the spray chamber is transported from bottom to top in the vertical direction during the spraying process.
[0060] In the present invention, the front end (bottom end) of the spray chamber is preferably provided with a distribution component so that the fiber ribbon is distributed into at least two fiber sub-ribbons before spraying; the distribution component is preferably a roller, more preferably a group of rollers, and the distribution component can be formed by several pairs of rollers.
[0061] In the present invention, rollers are arranged from the bottom to the top of the spray chamber, which are used to transport the fiber ribbons from bottom to top and to converge and squeeze the fiber ribbons through the rollers at the top; the rollers are preferably multiple.
[0062] In the present invention, the spray chamber is preferably further provided with a temperature control system for adjusting the temperature in the spray chamber. The present invention has no particular limitation on the temperature control system, and a temperature control device well known to those skilled in the art can be used to control the temperature in the spray chamber. In the present invention, the temperature control system is preferably an electric heating wire, such as a heating wire can be wound inside the spray chamber; the temperature control system is preferably a jacket, such as a jacket can be designed for the spray chamber to control the temperature by passing steam into the jacket.
[0063] In the present invention, a mixing chamber, a high-pressure pipeline and a nozzle are provided in the spray chamber. The mixing chamber is used to mix the crosslinking agent solution and the catalyst solution to form a crosslinking liquid. The outlet of the mixing chamber is connected to the inlet of the high-pressure pipeline, and the outlet of the high-pressure pipeline is connected to the inlet of the nozzle. In the present invention, the crosslinking liquid in the mixing chamber is transported to the nozzle through the high-pressure pipeline and sprayed from the nozzle onto the fiber ribbon. In the present invention, a plurality of nozzles are preferably provided in the spray chamber; the nozzles are provided on both sides of the fiber ribbon or the fiber sub-ribbon, and nozzles are provided on both sides of each fiber ribbon or the fiber sub-ribbon. In the present invention, the nozzle of the nozzle is preferably flat, and the length of the nozzle is preferably consistent with the width of the spray ribbon (fiber ribbon or fiber sub-ribbon), which is conducive to the uniform spraying of the crosslinking liquid on the fiber ribbon.
[0064] In the present invention, the structural schematic diagram of the spray chamber is as follows Figure 3 As shown, the spray chamber is vertically arranged, including: a mixing chamber 7, a high-pressure pipe 9 connected to the outlet of the mixing chamber, a nozzle 10 connected to the outlet of the high-pressure pipe, and a plurality of rollers 11 are arranged from the bottom to the top of the spray chamber shell 8, which are used to first distribute the fiber ribbon in the spray chamber into at least two fiber sub-ribbons, and transport them from bottom to top to the top, and gather the sprayed fiber sub-ribbons into one fiber ribbon at the top roller and extrude them; the nozzles are arranged on both sides of the fiber sub-ribbons in the middle of the spray chamber shell.
[0065] The present invention has no special limitation on the curing device, and any curing device well known to those skilled in the art can be used to cure the fiber ribbon after spraying.
[0066] The present invention has no special limitation on the water washing tank, and any water washing tank well known to those skilled in the art can be used to wash the cured fiber ribbon.
[0067] In the present invention, a fiber ribbon enters a vertically arranged spray chamber, and is divided into at least two fiber sub-ribbons by a plurality of pairs of rollers arranged at the bottom of the spray chamber. A cross-linking agent solution and a catalyst solution are mixed in a mixing chamber to form a cross-linking liquid, which is transported to a nozzle through a high-pressure pipeline. The nozzle sprays both sides of the fiber sub-ribbons. The fiber sub-ribbons move from bottom to top and converge at the rollers arranged at the top of the spray chamber for extrusion. The extruded fiber ribbons enter a curing device for curing, and then enter a water washing tank for washing.
[0068] The test method of the wet wear value (WAV) in the following embodiments of the present invention is: the nominal linear density D and the number of wet wear circles N of 20 fibers to be tested are simultaneously tested using Lenzing instruments' VIBROSKOP 500 fineness meter and DELTA 100 wet wear meter. The larger the wet wear value, the stronger the fiber's ability to resist fibrillation. The calculation formula of the wet wear value WAV (unit: r / dtex) is shown as follows:
[0069]
[0070] Example 1
[0071] This embodiment provides a structure such as Figure 2 The device for preparing cross-linked fibers shown comprises:
[0072] Spray room 4, curing equipment 5 and water washing tank 6;
[0073] The outlet of the spray room is connected to the inlet of the curing equipment; the outlet of the curing equipment is connected to the inlet of the water washing tank; the fiber ribbon enters the spray room, the curing equipment and the water washing tank in sequence;
[0074] The spray room is set vertically. The structural diagram of the spray room is as follows: Figure 3 As shown, it includes: a mixing chamber 7, a spray chamber shell 8, a high-pressure pipeline 9, a nozzle 10, and a roller 11;
[0075] The mixing chamber is used to mix the crosslinking agent solution and the catalyst solution to form a crosslinking liquid. The outlet of the mixing chamber is connected to the inlet of the high-pressure pipeline, and the outlet of the high-pressure pipeline is connected to the inlet of the nozzle. The crosslinking liquid in the mixing chamber is transported to the nozzle through the high-pressure pipeline and sprayed to spray the fiber sub-ribbon. There are multiple nozzles, which are arranged on both sides of the fiber sub-ribbon in the middle of the spray chamber shell. The nozzle opening of the nozzle is flat, and the length of the nozzle is the same as the width of the fiber sub-ribbon.
[0076] A plurality of rollers are arranged from the bottom to the top of the spray chamber shell, which are used to divide the fiber ribbon entering the spray chamber into at least two fiber sub-ribbons, transport the fiber ribbon from bottom to top, and gather and squeeze the fiber sub-ribbons after spraying; an electric heating wire is wound inside the spray chamber as a temperature control system to control the temperature of the spray chamber;
[0077] The extruded fiber ribbon enters the curing equipment for curing and then is washed in a water washing tank to obtain cross-linked fibers.
[0078] Example 2
[0079] The cross-linked fibers were prepared using the device provided in Example 1:
[0080] At 80°C, a mixed solution containing 1.84%wt TAHT (1,3,5-triacryloylhexahydro-1,3,5-triazine) and 2%wt sodium sulfate (the solvent in the mixed solution is water) was prepared and allowed to stand for 0 min, 15 min and 60 min respectively. A 6%wt Na3PO4 solution (the solvent in the solution is water) was prepared at 80°C. The mixed solution and the Na3PO4 solution were mixed in a mixing chamber at a mass ratio of 1:1 to form a cross-linking liquid, which was sprayed into a nozzle through a high-pressure pipe (the time from the beginning of mixing to spraying onto the fiber ribbon was no more than 10 seconds). The Lyocell fiber ribbon entered the spray chamber and was distributed into three fiber sub-ribbons at the bottom of the spray chamber through a number of rollers. Each fiber sub-ribbon had two sides. The fiber sub-ribbons were transported from bottom to top in the spray chamber. The cross-linking liquid sprayed from the nozzle penetrated the fiber sub-ribbons horizontally and sprayed along the fiber sub-ribbons. The ribbon flows downward naturally, and the cross-linking liquid is evenly sprayed on both sides of the fiber sub-ribbon; the fiber sub-ribbon is transported from bottom to top to the roller at the top of the spray chamber for convergence and extrusion, and the extruded cross-linking liquid flows naturally downward along the fiber ribbon (fiber sub-ribbon); during the spraying process, 0.653 kg of cross-linking liquid is sprayed on every 1 kg of net weight of fiber ribbon; the extruded fiber ribbon enters the curing equipment and is cured at 130°C for 35 minutes. The temperature of the fiber ribbon between spraying and curing treatment is 80°C, and then it enters the washing pool for washing and drying to obtain cross-linked fiber.
[0081] Comparative Example 1
[0082] use Figure 1 The cross-linked fiber preparation device of the structure shown in the figure prepares the cross-linked fiber, comprising:
[0083] Padding tank 1, curing equipment 2 and washing tank 3.
[0084] At 80°C, the lyocell fiber ribbon was dipped into a cross-linking solution (the solvent in the mixed solution was water) formed by a mixed solution of 0.92%wtTAHT, 1%wtNa2SO4 and 3%wtNa3PO4 which had been mixed for 0min, 15min and 60min for 10s, and the rolling rate was controlled at 125% (carried out in a dipping and rolling tank). The fiber was cured at 120°C for 30min (carried out in a curing device), washed with water (carried out in a washing tank) and dried to obtain cross-linked fibers.
[0085] The wet abrasion values of the cross-linked fibers prepared in Example 2 and Comparative Example 1 were tested according to the above method. The test results are as follows:
[0086] Cross-linking method 0min 15min 60min Comparative Example 1 620.19 302.57 44.55 Example 2 445.39 440.21 439.87
[0087] From the above results, it can be seen that the crosslinking effect of TAHT as a crosslinking agent and the crosslinking agent solution when left to stand for 60 minutes is only reduced by 1.24% compared with the spray method (Example 2) at 0 minutes. The fibers prepared in Example 2 all have a higher wet abrasion value WAV; the one-bath method (Comparative Example 1) decreased by 92.82%.
[0088] Example 3
[0089] The cross-linked fiber is prepared using the cross-linked fiber preparation device provided in Example 1:
[0090] At room temperature, a crosslinking agent solution containing 3%wt HMMM (methylated hexahydroxymethyl melamine resin) (the solvent in the solution is water) is prepared and allowed to stand for 0min, 15min and 60min respectively, and a p-toluenesulfonic acid solution with a concentration of 1.5%wt (the solvent in the solution is water) is prepared at room temperature; the crosslinking agent solution and the p-toluenesulfonic acid solution are mixed in a mixing chamber at a mass ratio of 1:1 to form a crosslinking liquid, which is sprayed into a nozzle through a high-pressure pipe (the time from the beginning of mixing to spraying onto the fiber ribbon is no more than 10 seconds); the Lyocell fiber ribbon enters the spray chamber and is distributed into three fiber sub-ribbons at the bottom of the spray chamber through a number of rollers, each of which has two sides. The fiber ribbons are transported from bottom to top in the room, and the cross-linking liquid sprayed from the nozzles penetrates the fiber ribbons horizontally and flows naturally downward along the fiber ribbons, and the cross-linking liquid is evenly sprayed on both sides of the fiber ribbons; the fiber ribbons are transported from bottom to top to the rollers at the top of the spray chamber for convergence and extrusion, and the extruded cross-linking liquid flows naturally downward along the fiber ribbons (fiber ribbons); during the spraying process, 0.333 kg of cross-linking liquid is sprayed for every 1 kg of net weight of the fiber ribbon; the extruded fiber ribbons enter the curing equipment and are cured at 115°C for 15 minutes, and the temperature of the fiber ribbons after spraying and before curing is room temperature (20-30°C), and then enter the washing pool for washing and drying to obtain cross-linked fibers.
[0091] Comparative Example 2
[0092] use Figure 1 The cross-linked fiber preparation device of the structure shown in the figure prepares the cross-linked fiber:
[0093] At room temperature, the fiber ribbon was dipped and rolled in a mixed solution of 3%wt HMMM and 1.5%wt p-toluenesulfonic acid (the solvent in the mixed solution was water) which had been mixed for 0min, 15min and 60min for 10s, three dips and three rolls, the rolling rate was controlled at 120% (carried out in a dipping and rolling tank), cured at 115°C for 15min (carried out in a curing device), washed with water (carried out in a washing tank) and dried to obtain cross-linked fibers.
[0094] The wet abrasion value of the cross-linked fibers prepared in Example 3 and Comparative Example 2 of the present invention was tested according to the above method. The test results are as follows:
[0095] Cross-linking method 0min 15min 60min Comparative Example 2 439.15 203.78 55.19 Example 3 401.57 398.57 388.67
[0096] From the data in the above table, it can be seen that HMMM as a cross-linking agent mixed with toluenesulfonic acid for fiber cross-linking treatment can also achieve good cross-linking effect, and its wet abrasion value WAV is as high as 400r / dtex.
[0097] Example 4
[0098] The cross-linked fiber is prepared using the cross-linked fiber preparation device provided in Example 1:
[0099] At 80°C, a mixed solution containing 3.6%wt TAHT (1,3,5-triacryloylhexahydro-1,3,5-triazine) and a certain concentration of sodium sulfate was prepared (the solvent in the mixed solution was water), and another mixed solution with a concentration of 3%wt was prepared at 80°C. Na3PO4 solution (the solvent in the solution is water); the above mixed solution and Na3PO4 solution are mixed in a mixing chamber at a mass ratio of 1:1 to form a cross-linking liquid, which is sprayed into a nozzle through a high-pressure pipeline (the time from the beginning of mixing to the spraying to the fiber ribbon does not exceed 10 seconds); the Lyocell fiber ribbon enters the spray chamber and is divided into three fiber sub-ribbons at the bottom of the spray chamber through a number of rollers, each fiber sub-ribbon has two sides, the fiber sub-ribbon is transported from bottom to top in the spray chamber, the cross-linking liquid sprayed from the nozzle horizontally penetrates the fiber sub-ribbon and naturally flows downward along the fiber sub-ribbon, and the cross-linking liquid is evenly sprayed on both sides of the fiber sub-ribbon; the fiber sub-ribbon is transported from bottom to top to the roller at the top of the spray chamber for convergence and extrusion, and the extruded cross-linking liquid flows naturally downward along the fiber ribbon (fiber sub-ribbon); 2kg of cross-linking liquid is sprayed for every 1kg net weight of the fiber ribbon during the spraying process; the extruded fiber ribbon enters the curing equipment and is cured at 120℃ for 30min, and the temperature of the fiber ribbon between the spraying and the curing treatment is 80℃, and then enters the washing tank for washing and drying to obtain cross-linked fibers.
[0100] The wet abrasion value of the cross-linked fibers prepared from sodium sulfate solutions of different concentrations was tested according to the above method, and the test results were as follows:
[0101] Sodium sulfate, wt Wet wear value, r / dtex 0 319.52 1% 390.63 2% 511.10 3% 421.47 4% 405.78
[0102] It can be seen that under certain conditions, the wet wear value is 511.10r / dtex when the sodium sulfate concentration is 2%wt, reaching the optimal value, which is 60% higher than that without adding sodium sulfate.
[0103] Example 5
[0104] The cross-linked fiber is prepared using the cross-linked fiber preparation device provided in Example 1:
[0105] At 70°C, a mixed solution containing 3.6%wt TAHT (1,3,5-triacryloylhexahydro-1,3,5-triazine) and 2%wt sodium sulfate was prepared (the solvent in the mixed solution was water), and different concentrations of Na3PO4 solutions (the solvent in the solution was water) were prepared at 70°C; the mixed solution and the Na3PO4 solution were mixed in a mixing chamber at a mass ratio of 1:1 to form a cross-linking liquid, which was sprayed into a nozzle through a high-pressure pipe (the time from the beginning of mixing to the spraying to the fiber ribbon was no more than 10 seconds); the Lyocell fiber ribbon entered the spray chamber and was divided into three fiber sub-ribbons at the bottom of the spray chamber by a number of rollers, each of which had two sides. The spray chamber transports from bottom to top, and the cross-linking liquid sprayed from the nozzle penetrates the fiber ribbon horizontally and flows downward naturally along the fiber ribbon, and the cross-linking liquid is evenly sprayed on both sides of the fiber ribbon; the fiber ribbon is transported from bottom to top to the roller at the top of the spray chamber for convergence and extrusion, and the extruded cross-linking liquid flows downward naturally along the fiber ribbon (fiber ribbon); during the spraying process, 0.417 kg of cross-linking liquid is sprayed for every 1 kg of net weight of the fiber ribbon; the extruded fiber ribbon enters the curing equipment and is cured at 110°C for 20 minutes. The temperature of the fiber ribbon between spraying and curing treatment is 70°C, and then it enters the washing tank for washing and drying to obtain cross-linked fibers.
[0106] The wet abrasion values of cross-linked fibers prepared with trisodium phosphate at different concentrations were tested according to the method described in the above technical solution. The test results are as follows:
[0107] Trisodium phosphate, wt Wet wear value, r / dtex 0 56.87 1% 162.85 2% 254.09 3% 319.52 4% 366.84 6% 307.8 8% 237.7
[0108] It can be seen that under certain conditions, the wet wear value increases with the increase of trisodium phosphate dosage. When the trisodium phosphate reaches 4%wt, the wet wear value reaches the optimal value.
[0109] Example 6
[0110] The cross-linked fiber is prepared using the cross-linked fiber preparation device provided in Example 1:
[0111] At 80°C, a mixed solution containing 3.6%wt TAHT (1,3,5-triacryloylhexahydro-1,3,5-triazine) and 2%wt sodium sulfate was prepared (the solvent in the mixed solution was water), and another solution with a concentration of 3%wt was prepared at 80°C. Na3PO4 solution (the solvent in the solution is water); the above mixed solution and Na3PO4 solution are mixed in a mixing chamber at a mass ratio of 1:1 to form a cross-linking liquid, which is sprayed into a nozzle through a high-pressure pipeline (the time from the beginning of mixing to the spraying to the fiber ribbon does not exceed 10 seconds); the Lyocell fiber ribbon enters the spray chamber and is divided into three fiber sub-ribbons by a number of rollers at the bottom of the spray chamber. Each fiber sub-ribbon has two sides. The fiber sub-ribbon is transported from bottom to top in the spray chamber. The cross-linking liquid sprayed from the nozzle horizontally penetrates the fiber sub-ribbon and flows naturally downward along the fiber sub-ribbon. The cross-linking liquid is evenly sprayed on both sides of the fiber sub-ribbon; the fiber sub-ribbon is transported from bottom to top to the roller at the top of the spray chamber for convergence and extrusion. The extruded cross-linking liquid flows naturally downward along the fiber ribbon (fiber sub-ribbon); during the spraying process, different masses of cross-linking liquid are sprayed on every 1kg net weight of the fiber ribbon; the extruded fiber ribbon enters the curing equipment and is cured at 120°C for 30 minutes. The temperature of the fiber ribbon during the process between spraying and before curing is 80°C, and then enters the washing tank for washing and drying to obtain cross-linked fibers.
[0112] The wet abrasion value of the cross-linked fibers prepared with different spray qualities was tested according to the method described in the above technical solution, and the strength was tested according to the standard GB / T 14337-2008 "Test Method for Tensile Properties of Chemical Staple Fibers". The test results are as follows:
[0113] Cross-linking liquid quality / fiber ribbon quality Wet wear value, r / dtex Strength, cN / dtex 0.33 178.77 4.39 0.35 204.78 4.25 0.49 252.43 4.18 0.61 298.76 4.11 0.70 334.67 4.05 0.92 389.75 3.96 1.03 414.86 3.91 1.12 439.54 3.52 1.31 476.52 3.31
[0114] It can be seen from the test results that the higher the dosage of spray cross-linking liquid, the better the cross-linking effect, but the fiber strength decreases and the cost increases. Considering the cross-linking effect, fiber strength and cost and other factors comprehensively, when the cross-linking liquid mass / fiber ribbon mass is 1.03, the optimal process is reached. At this time, the fiber wet wear value is 414.86r / dtex and the fiber strength is 3.91cN / dtex.
[0115] Comparative Example 3
[0116] At 80°C, a mixed aqueous solution containing 3.6%wt TAHT (1,3,5-triacryloylhexahydro-1,3,5-triazine) and 2%wt sodium sulfate is prepared, and a 3%wt Na3PO4 aqueous solution is prepared at 80°C; the mixed solution and the Na3PO4 solution are mixed in a mixing chamber at a mass ratio of 1:1 to form a cross-linking liquid, which is sprayed into a nozzle through a high-pressure pipeline (the time from the beginning of mixing to the spraying to the fiber ribbon does not exceed 10 seconds); the Lyocell fiber ribbon enters the spray chamber and is divided into three fiber sub-ribbons at the bottom of the spray chamber through a number of rollers, each fiber sub-ribbon has two sides, and the fiber sub-ribbons are transported from bottom to top in the spray chamber. The cross-linking liquid sprayed from the nozzle horizontally penetrates the fiber sub-ribbon and flows naturally downward along the fiber sub-ribbon (vertical spraying), and the cross-linking liquid is evenly sprayed on both sides of the fiber sub-ribbon; the fiber sub-ribbons are transported from bottom to top to the roller at the top of the spray chamber for convergence and extrusion, and the extruded cross-linking liquid flows naturally downward along the fiber ribbon (fiber sub-ribbon); or
[0117] The fiber ribbon is transported from left to right during the spraying process (horizontal spraying, the spray chamber is set horizontally), and the fiber ribbon moves to the right to the roller for squeezing;
[0118] During the spraying process, 1.03 kg of cross-linking liquid is sprayed on every 1 kg of net weight of fiber ribbon; then it enters the curing equipment and is cured at 120°C for 30 minutes. The temperature of the fiber ribbon between the spraying and the curing treatment is 80°C. Then it enters the washing tank for washing and then is dried to obtain cross-linked fibers.
[0119] The wet abrasion values of the cross-linked fibers prepared by vertical spraying and horizontal spraying were tested according to the method described in the above technical solution. The test results are as follows:
[0120] Spraying method Wet wear value, r / dtex Vertical spray 414.86 Horizontal spray 357.57
[0121] It can be seen from the test results that vertical spraying effectively improves the utilization rate of the cross-linking agent mixed solution. Compared with horizontal spraying, better cross-linking effect can be obtained under the same conditions.
[0122] The method provided by the present invention solves the problem of large amount of crosslinking liquid wasted due to mixed hydrolysis and self-polymerization of the crosslinking agent and the catalyst, has low equipment requirements and simple operation, effectively improves the crosslinking effect and reduces production costs.
[0123] The above is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements and modifications without departing from the principle of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.
Claims
1. A method for preparing a lyocell cross-linked fiber, comprising: The crosslinking liquid formed by mixing the crosslinking agent solution and the catalyst solution is immediately sprayed on the fiber ribbon, and the time from the formation of the crosslinking liquid to the spraying of the crosslinking liquid on the fiber ribbon does not exceed 10 seconds; then the fiber ribbon after spraying is cured to obtain Lyocell crosslinked fiber; The crosslinking agent in the crosslinking agent solution is selected from 1,3,5-triacryloylhexahydro-1,3,5-triazine; or, the crosslinking agent in the crosslinking agent solution is selected from methyl etherified hexamethylol melamine resin; The spraying also includes: Distributing the fiber ribbon into at least two fiber sub-ribbons, each fiber sub-ribbon having two sides; spraying the cross-linking liquid on both sides of each fiber sub-ribbon during the spraying process; The curing process also includes: The fiber ribbon after spraying is subjected to extrusion treatment; During the process between spraying and squeezing, the fiber ribbon moves from bottom to top in a direction parallel to the fiber ribbon, so that the squeezed cross-linking liquid naturally flows downward along the fiber ribbon.
2. The method according to claim 1, characterized in that The crosslinking agent in the crosslinking agent solution is selected from 1,3,5-triacryloylhexahydro-1,3,5-triazine; the catalyst in the catalyst solution is selected from one or more of sodium hydroxide, trisodium phosphate and sodium carbonate.
3. The method according to claim 1, characterized in that The crosslinking agent in the crosslinking agent solution is selected from methylated hexamethylolmelamine resin; the catalyst in the catalyst solution is selected from one or more of methanesulfonic acid, p-toluenesulfonic acid and dodecylbenzenesulfonate.
4. The method according to claim 2, characterized in that: The mass ratio of the fiber ribbon, the crosslinking agent in the crosslinking agent solution and the catalyst in the catalyst solution is 100:(0.1-7):(0.1-13).
5. The method according to claim 3, characterized in that: The mass ratio of the fiber ribbon, the crosslinking agent in the crosslinking agent solution and the catalyst in the catalyst solution is 100:(0.1-10):(0.6-8).
6. The method according to claim 2, characterized in that The temperature of the fiber ribbon during the process between spraying and curing is 65-85°C.
7. The method according to claim 2, characterized in that Also includes: Sodium sulfate was added to the crosslinker solution.
8. A preparation device used in the method for preparing the Lyocell cross-linked fiber according to any one of claims 1 to 7, comprising: A spray room, used to spray the cross-linking liquid immediately on the fiber ribbons; The crosslinking agent in the crosslinking agent solution is selected from 1,3,5-triacryloylhexahydro-1,3,5-triazine; or, the crosslinking agent in the crosslinking agent solution is selected from methyl etherified hexamethylol melamine resin; A curing device having an inlet connected to the outlet of the spray chamber, wherein the fiber ribbon enters the curing device from the spray chamber; A water washing tank having an inlet connected to the outlet of the curing device, wherein the fiber ribbon enters the water washing tank from the curing device; The spray chamber is arranged vertically, so that the fiber ribbon enters the spray chamber and is transported vertically from bottom to top along the bottom end to the top end of the spray chamber; The bottom end of the spray chamber is provided with a distribution assembly, so that the fiber ribbon is distributed into at least two fiber sub-ribbons after entering the spray chamber; A plurality of nozzles are arranged in the spray chamber, and nozzles are arranged on both sides of each fiber sub-ribbon; The spray chamber is provided with a temperature control system for adjusting the temperature in the spray chamber.
Citation Information
Patent Citations
Barrel-shaped open-width knitted fabric washing device
CN103789948A
System and method for producing cross-linking lyocell
CN108360182A
Preparation method of non-fibrillated Lyocell fiber
CN110924153A
Lyocell fiber, Lyocell fiber antigen fibrillation cross-linking agent, and method for treating Lyocell fiber antigen fibrillation
CN112458752A
Cross-linked cellulose fibers and method of making same
CN1886556A